2022
DOI: 10.1186/s12889-022-14087-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of general and abdominal obesity and hypertension in rural and urban residents in Bangladesh: a cross-sectional study

Abstract: Background Obesity and hypertension are global health concerns. Both are linked with increased risks of all-cause and cardiovascular mortality. Several early studies reported the prevalence of obesity and hypertension in Bangladeshi adults, but the associated factors in this country population are not clear yet. We aimed to estimate the prevalence and related risk factors of general and abdominal obesity and hypertension in rural and urban adults in Bangladesh. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 54 publications
4
16
0
Order By: Relevance
“…These observed differences highlights that there may be additional demographic, lifestyle, and biological risk factors for obesity that should be analyzed. Many of these risk factors have been examined in the literature, including increased intake of sugar, decreased exercise, increased sedentary activity, and decreased sleep 11,13,14,16,29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observed differences highlights that there may be additional demographic, lifestyle, and biological risk factors for obesity that should be analyzed. Many of these risk factors have been examined in the literature, including increased intake of sugar, decreased exercise, increased sedentary activity, and decreased sleep 11,13,14,16,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have identi ed major risk factors for obesity, including demographic factors (race, sex, age), lifestyle factors (exercise, sleep), and clinical comorbidities (hypertension, diabetes. Additionally, multiple studies have demonstrated the high prevalence of weight gain in the United States population and detailed the signi cant medical consequences of obesity related diseases such as coronary artery disease and type II diabetes [11][12][13][14][15][16][17] . Despite the recognition of long-term weight gain as an important public health issue, there is a paucity of studies studying the long-term weight gain and building models for long-term projection.…”
Section: Introductionmentioning
confidence: 99%
“…Anthropometric data including age, sex, height, weight, waist circumference (WC) and hip circumference (HC) were recorded in a structured questionnaire form following the standard procedures described elsewhere [ 25 31 ]. Height was measured to the nearest 0.1 cm using a measuring tape and weight was measured to the nearest 0.1 kg by a digital electronic LCD weighing machine (Beurer 700, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Anthropometric data like weight, height, waist circumferences (WC) and hip circumferences (HC) were measured following a standard procedure described elsewhere 24 31 . Participants’ health status-related information such as the presence of hypertension, diabetes mellitus, and other chronic diseases were also recorded in the questionnaire form.…”
Section: Methodsmentioning
confidence: 99%